The Effect of Total Quality Management Practices on Operational Efficiency in Textile Industries in Solo - Fitriana, Desita Putri (Maroon Journal De Management, 2025)
The textile industry in Solo is increasingly challenged by global competition, pushing companies to enhance efficiency and maintain superior product quality. Total Quality Management (TQM) serves as an integrated management framework that emphasizes leadership commitment, employee participation, customer orientation, continuous improvement, and systematic quality assessment. This study investigates the impact of TQM implementation on operational efficiency among medium and large-scale textile industries in Solo. A quantitative correlational design was applied, involving 180 respondents comprising managers and employees selected through proportional stratified random sampling. Data were collected using structured questionnaires that assessed TQM dimensions and operational efficiency indicators on a five-point Likert scale. Statistical analysis using descriptive methods, Pearson correlation, and linear regression in IBM SPSS version 25 demonstrated that TQM practices are positively perceived, particularly in leadership commitment and employee involvement. Operational efficiency also showed strong performance in timeliness and product quality, though waste minimization remains a challenge. The correlation coefficient (r = 0.671, p < 0.01) and regression results indicated that TQM significantly explains 45.2% of efficiency variance. Overall, the findings highlight that TQM substantially enhances operational efficiency, underscoring the need to strengthen continuous improvement and waste reduction initiatives to sustain global competitiveness.